The Prevention of Financial Distress on Banking Financial Performance in Indonesia - Shendy Amalia; Darwis Agustriana; Neneng Susanti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The banking industry in Indonesia is currently experiencing a big paradigm, where the role of banking is currently experiencing a shift. Threats to bank business performance are also increasing in line with slowing economic growth and potential sectors for bank business. The purpose of this study is to determine the effect of credit risk (Non Performing Financing / NPF), liquidity risk (Financing to Deposit Ratio / FDR), value commposit of Good Corporate Governance, Operational Costs to Operational Income (BOPO), Net Operating Margin (NOM) and Capital Adequacy Ratio (CAR) on Banking Financial Performance in Indonesia. The research method used is descriptive and verification methods, while the statistical analysis method uses multiple regression with eviews 10 software.The population used in this study is banking companies listed on the Stock Exchange for the 2014-2018 period and samples were taken using purposive sampling technique so that the research sample was 32 companies. The data is taken from Bank Indonesia (www.bi.go.id), Financial Fervices Authority (www.ojk.go.id) and the official website of the bank concerned. Based on the research results, (Non Performing Financing / NPF, GCG, Operations on Operating Income (BOPO) has an influence on temporary banking performance (Financing to Deposit Ratio / FDR), Net Operating Margin (NOM) and Capital Adequacy Ratio (CAR) have no effect. on banking performance.